2011
DOI: 10.1136/gut.2010.229104
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for accelerated colorectal adenoma–carcinoma progression inMUTYH-associated polyposis?

Abstract: The high risk of developing CRC under surveillance in patients with MAP may suggest an accelerated carcinogenesis. Surveillance of these patients should therefore include colonoscopy at short intervals, for example, at 1-2-year intervals starting from the age of 18 to 20 years. If surgery for CRC is warranted, a (sub)total colectomy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 24 publications
3
52
0
1
Order By: Relevance
“…We revealed that MAP adenomas have approximately two to four times the number of coding region somatic mutations when compared to FAP adenomas, and that these mutations are overwhelmingly G:C → T:A mutations, in keeping with the expected signature associated with MUTYH loss. This observation confirms, for the first time, the expectation that deficiency of MUTYH leads to a mutator phenotype in colorectal tumours, and is consistent with the observation of substantial colorectal cancer risk in MAP, even in the absence of dense polyposis 35. We find significant complexity in the patterns of mutated genes, such that, with the exception of APC , KRAS and WTX mutations, few adenomas have the same set of mutated driver genes, a novel observation that may have implications for the definition of high‐risk adenomas in the era of molecular pathology.…”
Section: Discussionsupporting
confidence: 90%
“…We revealed that MAP adenomas have approximately two to four times the number of coding region somatic mutations when compared to FAP adenomas, and that these mutations are overwhelmingly G:C → T:A mutations, in keeping with the expected signature associated with MUTYH loss. This observation confirms, for the first time, the expectation that deficiency of MUTYH leads to a mutator phenotype in colorectal tumours, and is consistent with the observation of substantial colorectal cancer risk in MAP, even in the absence of dense polyposis 35. We find significant complexity in the patterns of mutated genes, such that, with the exception of APC , KRAS and WTX mutations, few adenomas have the same set of mutated driver genes, a novel observation that may have implications for the definition of high‐risk adenomas in the era of molecular pathology.…”
Section: Discussionsupporting
confidence: 90%
“…To improve clinical identification of affected patients endoscopists as well as gastroenterologists, oncologists and abdominal surgeons must -in addition to other hereditary CRC syndromes (e.g., Lynch-Syndrome or APC mutation positive FAP)-be aware of MUTYH-associated disease. Because of the high lifetime relative risk of developing CRC in biallelic mutation carriers (63% develop CRC until the age of 60 [31]; odds ratio 28 [28]) and the high risk of developing CRC under surveillance [31] specific follow-up is needed for MAP patients (follow-up colonoscopies at shorter intervals, more aggressive surgery, screening for extracolonic manifestations) and their potentially affected but asymptomatic siblings (genetic testing, CRC prevention strategies). Whereas biallelic mutation carriers obviously benefit from timely identification it is unclear whether testing-associated anxiety may overcome advantages in monoallelic mutation carriers with only slightly elevated CRC risk [7,[12][13][14][15]28] compared to patients carrying wild-type alleles.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, MUTYH-associatedpolyposis cancers appear to follow a distinct pathway compared to other colorectal cancers: some features overlap with chromosomal instability colorectal cancer phenotype, including frequent APC and KRAS mutations, 9,13 some others with microsatellite instability phenotype, including loss of HLA class I protein expression. 14 Recently, Nieuwenhuis and collaborators 15 have suggested the occurrence of an accelerated disease progression in MUTYH-associated-polyposis, underlying the high risk for patients to develop colorectal cancer even under surveillance.…”
mentioning
confidence: 99%